Concept of Position and Role People's Consultative Assembly as an Embodiment of People's Sovereignty in the State System in Indonesia - Ari Wibowo; Eni Dasuki Suhardini; Dani Durahman (Greenation International Journal of Law and Social Sciences, 2026)
The People's Consultative Assembly (MPR) is a state institution classified as a bicameral legislative institution in the constitutional system in Indonesia, with a membership composition consisting of members of the DPR and DPD. Condition gives rise to several potential problems, including conflicts of interest in carrying out their duties and authorities, so that it will be difficult to realize a people's sovereign democracy. It shows that first, the current position of the MPR is not related to a people's sovereign democracy, because there is a distortion of interests between the interests of the people and the interests of political parties, making it difficult for the MPR to accommodate the interests of the people. The importance of restructuring the position and role of the MPR to guarantee the upholding of the supremacy of democracy and the supremacy of the constitution, as mandated by the 1945 Constitution of the Republic of Indonesia.